2020
DOI: 10.1364/ol.412349
|View full text |Cite
|
Sign up to set email alerts
|

Fine features of optical potential well induced by nonlinearity

Abstract: Particles trapped by optical tweezers, behaving as mechanical oscillators in an optomechanical system, have found tremendous applications in various disciplines and are still arousing research interest in frontier and fundamental physics. These optically trapped oscillators provide compact particle confinement and strong oscillator stiffness. But these features are limited by the size of the focused light spot of a laser beam, which is typically restricted by the optical diffraction limit. Here, we propose to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Compared to the previous methods that formed an orbit, such as schemes with nanofabrication or a laser beam with a particular phase structure, the method we proposed here is much simpler by applying a circularly polarized femtosecond Gaussian laser beam. Previous results have shown that a pair of point-like potential wells could be formed for nonlinear particles when the linearly-polarized femtosecond laser power exceeds a transition power 35 37 . By rotating the linear polarization of the laser, such potential-well pair could be rotated accordingly, thus resulting in subsequent circular movement of the trapped particle within the well.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the previous methods that formed an orbit, such as schemes with nanofabrication or a laser beam with a particular phase structure, the method we proposed here is much simpler by applying a circularly polarized femtosecond Gaussian laser beam. Previous results have shown that a pair of point-like potential wells could be formed for nonlinear particles when the linearly-polarized femtosecond laser power exceeds a transition power 35 37 . By rotating the linear polarization of the laser, such potential-well pair could be rotated accordingly, thus resulting in subsequent circular movement of the trapped particle within the well.…”
Section: Resultsmentioning
confidence: 99%
“…Another experiment, however, showed that the distance between the potential minima was determined by the distribution of the longitude electromagnetic field of the focused beam . Further investigations are still needed with these systems for optical manipulation involving the nonlinearity. ,, Apart from the particle nonlinearity, a particle with linear permittivity locating in the nonlinear surrounding medium can also show the exotic pulling force . Therefore, more efforts considering the degree of freedom of nonlinearity are of necessary for optical manipulation in some physical scenarios.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…Optical tweezers have found tremendous application in various areas, including colloidal sciences, chemistry, and biophysics since their invention several decades ago. [1][2][3][4][5] However, high numerical aperture and large incident intensity are required to get enough optical force when nanoparticles need to be manipulated. This also may damage the biological cell or specimen due to the heat generated by large incident power.…”
Section: Introductionmentioning
confidence: 99%